Pengaruh Pelatihan Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Salmanda Jaya Utama - Achmad Zulfikar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
PT Salmanda Jaya Utama is a franchise of Shell Indonesia which is engaged in the business of fuel oil (BBM), lubricants for industry, automotive, transportation, mini market (select). Research shows that improving abilities and skills through training will increase employee effectiveness and efficiency. And a well-structured organization can achieve optimal work results. The purpose of this study was to determine the training and organizational culture affect employee performance. The method of collecting data in preparing the thesis is the observation method, interviews, primary data with the analysis method in the form of quantitative, namely the multiple linear regression analysis method with a saturated sample technique totaling 40 employees. The results of this study state that training partially has a positive and significant effect on employee performance with a significance level of 0.008 <0.05 and a T value> T table of 2.789> 2.022. Organizational culture partially has a positive and significant effect on employee performance with a significant level of 0.000 <0.05 and the value of T count> T table of 5.528> 2.022. Training and organizational culture simultaneously have a positive and significant effect on employee performance with a value of F count> F table of 59.391> 3.24